La aplicación de estándares de protección de inversiones extranjeras. Una mirada desde los casos argentinos (2014)
The guidelines of the Washington Covenant in the 90s, involved the political and economic transformation of the Latin American states due to the liberalization of the economy, government reform, deregulation and privatization. Following these guidelines, the term “foreign investment” became an imperative for economic growth and development, so that the states to achieve such purposes resorted to bilateral solutions, modifying national legislation and signing Bilateral Investment Treaties (bit). The incorporation of a series of protection standards as fair treatment, expropriation clauses, most favored nation, as a condition for the participation of foreign investors in the public services of the states, are a clear example of this new reality. The system for the promotion and protection of foreign investment has been becoming a new “subsystem” international law, with its own rules and its own enforcement mechanism for dispute resolution through international arbitration tribunals, although in some where collision States constitutional standards.